Comprehensive Account on the Synthesis of (-)-Balanol and its Analogues - Ahmad, Sajjad; Akhtar, Rabia; Zahoor, Ameer F. (Current Organic Synthesis, 2022)
Background: A variety of diseases have been associated with hyperactivation of protein kinase C (PKC) enzymes such as cancer, diabetes, asthma, cardiovascular and central nervous system disorders. There is a dire need to selectively inhibit these enzymes by synthesizing new potent inhibitors. Balanol, a fungal metabolite belonging to the PKC inhibitor family, is especially included in this aspect. Tremendous effort has been put towards the synthesis of balanol by different research groups. Objectives: The aim of this review is to provide a detailed description of synthetic approaches adopted for the synthesis of key fragments of balanol (azepane and benzophenone). All the factors that resulted in excellent yield and high enantioselectivity have also been mentioned. Conclusion: It has been shown throughout this review that the synthesis of hexahydroazepine and benzophenone cores of balanol was achieved by employing a variety of important key steps with commercially available starting precursors, which make this total synthesis more valuable. Moreover, this article provides ideas to the synthetic as well as pharmaceutical chemists for the synthesis of (-)-balanol and its analogues.
Keywords: Protein kinase C